(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the customer satisfaction of Café Kusina restaurant using the DINESERV model in terms of reliability, assurance, tangibility, empathy, and responsiveness. The results of the study reveal that the assessment of Customer Satisfaction of Café Kusina was “very satisfied” in terms of product and place; the utilization of the DINESERV model in assessing the customer satisfaction of Café Kusina “strongly agrees” with terms of tangibility, empathy, and responsiveness; the most common problem encountered by the customers of Café Kusina was there are no enough parking lots; and there is a guideline proposed by the researchers to improve the customer satisfaction of Café Kusina based on the result of DINESERV model. Based on the result presented, the following are the recommendations: maintain their atmosphere where customers will still feel comfortable; adding and offering coupons and discounts could make the customers more satisfied; consider planning on providing parking space for customers; and implement new guidelines that could help and improve the customer satisfaction of Cafe Kusina.